(untitled) - Dheeraj Jain; Sivaraman A; Balasubramaniam (Asian Journal of Medical Research, 2019)
Background: To study the clinical profile of patients with diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic state (HHS) and their outcome in a tertiary care hospital in Puducherry.Subjects and Methods:This was a retrospective study of patients with DKA and HHS admitted in Indira Gandhi Medical College & Research Institute (IGMCRI), Puducherry over a period of two years. Data on precipitating factors, clinical features, serum electrolytes, duration of hospital stay and mortality were obtained.Results:100 patients were included in the study. 84 patients had DKA and 16 patients had HHS. Of the 84 patients with DKA 65 (77.4%) were diagnosed as Type 1 DM and 19 patients as Type 2 DM (22.4%). Commonest precipitating factor for DKA was missed treatment (61%) followed by Infection. Total number of deaths in DKA was 9. Out of 19 type 2 patients with DKA,5 expired which was much higher to those to with type l DM with DKA (4 out of 65). The commonest cause of death was infectious (sepsis related) cause, with UTI being the commonest (40%). In HHS patients the mean age of presentation was 68.3. HHS was associated with higher mortality compared to DKA. Coma, altered sensorium (6 out of 16), seizures (4 out of 16) was seen in significant number of patients with HHS. BU, creatinine, osmolality was significantly elevated in patients with HHS who expired compared to survivors. Most common cause of death in HHS was sepsis (infection) related with UTI (40%).Conclusion: DKA is common in patients with T2DM in our setup. Over 50% of the patients presenting with DKA or HHS have no previous diagnosis of DM. Infections and noncompliance are important precipitants of hyperglycaemic emergencies.